Prevalence and factors associated with late HIV diagnosis. Issue 6 (10th March 2015) - Dai, Se‐Ying; Liu, Jin‐Ji; Fan, Yin‐Guang; Shan, Gui‐Su; Zhang, Hong‐Bo; Li, Ming‐Qiang; Ye, Dong‐Qing
<x xml:space="preserve">Abstract</x> While highly active antiretroviral therapy has been successful in delaying progression into AIDS, late HIV diagnosis remains a major contributor to the mortality and morbidity of AIDS. An epidemiological study was conducted to evaluate the prevalence and factors of late diagnosis and the characteristics of those individuals with late diagnosis in Liuzhou city. Patients with late diagnosis were defined as either those who were diagnosed with AIDS at the time of HIV diagnosis or as those who developed AIDS no more than 1 year after HIV diagnosis. Of 899 participants, 72.6% had a late diagnosis. Common characteristics of those who experienced late diagnosis included older participants, those who were unexpectedly diagnosed while seeking other medical attention, participants who believed they could not acquire HIV from their regular heterosexual partners, those who never considered getting tested for HIV, and patients with unexplained weight loss, angular cheilitis, or prolonged fever prior to HIV diagnosis. On the other hand, those participants who were diagnosed via testing at compulsory rehabilitation centers and those whose annual household income was greater than 30, 000 Yuan were less likely to be diagnosed late. These results suggested that late HIV diagnosis is common in Liuzhou city, and it is essential to promote appropriate strategies to detect HIV infections earlier. Strategies that require HIV/AIDS patients to notify their spouse/sexual‐partners about their HIV‐positive results within one month and start provider‐initiated HIV testing and counseling in medical facilities are beneficial to earlier HIV diagnosis. J. Med. Virol. 87:970–977, 2015. © 2015 Wiley Periodicals, Inc.